Endothelial Poldip2 regulates sepsis-induced lung injury via Rho pathway activation . Issue 11 (16th September 2021) - Dolmatova, Elena V; Forrester, Steven J; Wang, Keke; Ou, Ziwei; Williams, Holly C; Joseph, Giji; Kumar, Sandeep; Valdivia, Alejandra; Kowalczyk, Andrew P; Qu, Hongyan; Jo, Hanjoong; Lassègue, Bernard; et al.
Abstract: Aims: Sepsis-induced lung injury is associated with significant morbidity and mortality. Previously, we showed that heterozygous deletion of polymerase δ-interacting protein 2 (Poldip2) was protective against sepsis-induced lung injury. Since endothelial barrier disruption is thought to be the main mechanism of sepsis-induced lung injury, we sought to determine if the observed protection was specifically due to the effect of reduced endothelial Poldip2. Methods and results: Endothelial-specific Poldip2 knock-out mice (EC−/−) and their wild-type littermates (EC+/+) were injected with saline or lipopolysaccharide (18 mg/kg) to model sepsis-induced lung injury. At 18 h post-injection mice, were euthanized and bronchoalveolar lavage (BAL) fluid and lung tissue were collected to assess leucocyte infiltration. Poldip2 EC−/− mice showed reduced lung leucocyte infiltration in BAL (0.21 ± 0.9×10 6 vs. 1.29 ± 1.8×10 6 cells/mL) and lung tissue (12.7 ± 1.8 vs. 23 ± 3.7% neutrophils of total number of cells) compared to Poldip2 EC+/+ mice. qPCR analysis of the lung tissue revealed a significantly dampened induction of inflammatory gene expression (TNFα 2.23 ± 0.39 vs. 4.15 ± 0.5-fold, IκBα 4.32 ± 1.53 vs. 8.97 ± 1.59-fold), neutrophil chemoattractant gene expression (CXCL1 68.8 ± 29.6 vs. 147 ± 25.7-fold, CXCL2 65 ± 25.6 vs. 215 ± 27.3-fold) and a marker of endothelial activation (VCAM1 1.25 ± 0.25 vs. 3.8 ± 0.38-fold) in Poldip2 EC−/− compared to Poldip2 EC+/+ lungs. An in vitro model using human pulmonary microvascular endothelial cells was used to assess the effect of Poldip2 knock-down on endothelial activation and permeability. TNFα-induced endothelial permeability and VE-cadherin disruption were significantly reduced with siRNA-mediated knock-down of Poldip2 (5 ± 0.5 vs. 17.5 ± 3-fold for permeability, 1.5 ± 0.4 vs. 10.9 ± 1.3-fold for proportion of disrupted VE-cadherin). Poldip2 knock-down altered expression of Rho-GTPase-related genes, which correlated with reduced RhoA activation by TNFα (0.94 ± 0.05 vs. 1.29 ± 0.01 of relative RhoA activity) accompanied by redistribution of active-RhoA staining to the centre of the cell. Conclusion: Poldip2 is a potent regulator of endothelial dysfunction during sepsis-induced lung injury, and its endothelium-specific inhibition may provide clinical benefit. Graphical Abstract: